Impact of Dietary Protein Reduction on Broiler Performance, Carcass Composition, and Meat Quality - Mostafa, Iman; Barari, Mohammad; Asasi , Keramat (Journal of Poultry Sciences and Avian Diseases, 2025)
Protein is a crucial nutrient in poultry nutrition, influencing growth, metabolism, and carcass composition. Optimizing dietary crude protein (CP) levels while ensuring adequate amino acid supplementation is essential for maximizing broiler performance and economic efficiency. This study evaluated the effects of reducing dietary CP levels on broiler growth performance, feed efficiency, carcass composition, and meat quality. A total of 150 one-day-old Ross 308 broilers were randomly assigned to three dietary treatments: low protein (LP), medium protein (MP), and high protein (HP). The LP group received 18%-16%-14% CP, the MP group received 20%-18%-16% CP, and the HP group received 22%-20%-18% CP across different growth phases. Results indicated that the HP group achieved the highest final body weight (2.78 kg), followed by the MP (2.53 kg) and LP (2.29 kg) groups (p